METHODOLOGICAL AND PSYCHOLOGICAL ASPECTS OF EDUCATION FOR SUSTAINABLE DEVELOPMENT IN RUSSIA WITH REGARD TO INTERNATIONAL COOPERATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In 2004 the European Economic Commission developed the Strategy of Education for Sustainable Development (ESD). The aim of the strategy is the promotion of education for sustainable development and its inclusion in the system of formal and informal education. The authors propose the measures for the acceleration of ESD distribution at the international level because international cooperation in education can be considered as a contribution of countries to the implementation of global transition to sustainable development. The authors’ concept of the phenomenon of ecological consciousness and the conditions of its formation are considered. The main problems of ESD efficiency are defined and criteria for its evaluation are offered. Integral features of the personality as an indispensable component of ESD are described.